Development of Lokal Wisdom-Based “Daily Say’s” Learning Media in English Learning for Grade 4 of Trembes State Elementary School - Mufaricha Ulia Anjani; Suttrisno; Nurul Mahruzah Yulia (Global Action and Education for Society, 2025)
The lack of innovation learning media at SD Negeri Trembes causes low interest and understanding of students towards English subjects, low knowledge of students towards local wisdom in their environment is also a problem that needs attention. This study aims to develop learning media